2012
DOI: 10.1530/eje-11-1047
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose estrogen combined oral contraceptives may negatively influence physiological bone mineral density acquisition during adolescence

Abstract: Background: The aim was to evaluate changes of bone mineral density (BMD) and markers of bone turnover in healthy adolescents, and in adolescent users of combined oral contraceptives (COCs) with different ethinylestradiol (EE) contents. Methods: In this prospective crossover study, 56 healthy females (15-19.5 years) with desire to use hormonal contraception were randomized to COC with either 30 or 15 mg of EE in crossover design of 9-month intervention each in reverse order. Nonusers of the same age (nZ28) ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 37 publications
0
23
2
5
Order By: Relevance
“…Further studies are necessary to determine whether lower doses of ethinyl estradiol may cause lesser increases in SHBG, and therefore cause different impacts on bone. Cibula and colleagues reported lower BMD with the 15‐μg vs. the 30‐μg ethinyl estradiol COC formulation in adolescent girls. Scholes and colleagues found a trend for lower BMD with longer duration of use and lower estradiol dose formulations in young women.…”
Section: Discussionmentioning
confidence: 98%
“…Further studies are necessary to determine whether lower doses of ethinyl estradiol may cause lesser increases in SHBG, and therefore cause different impacts on bone. Cibula and colleagues reported lower BMD with the 15‐μg vs. the 30‐μg ethinyl estradiol COC formulation in adolescent girls. Scholes and colleagues found a trend for lower BMD with longer duration of use and lower estradiol dose formulations in young women.…”
Section: Discussionmentioning
confidence: 98%
“…98 In adolescent girls, low-dose oral contraceptives containing less than 30 μg of ethinyl estradiol may interfere with peak bone mass acquisition compared with oral contraceptives containing ≥30 μg of ethinyl estradiol. 99,100 Despite a possible reduction in BMD in oral contraceptive users, a recent Cochrane review of observational studies found no association between oral contraceptive use and increased fracture risk. 101 …”
Section: Secondary Prevention: Assessment Of Populations At Risk For mentioning
confidence: 99%
“…Doses of estrogen less than 30 mg reduce BD accumulation, with the lowest-dose estrogen (15 mg) having the most profound effect (Cibula, Skrenkova, Hill, & Stepan, 2012). This difference is most likely clinically insignificant, because the BD of adolescents taking CHCs is well above the fracture threshold (Gersten, Hsieh, Weiss, & Ricciotti, 2016).…”
Section: Bd Concernsmentioning
confidence: 99%